Reform of the Debt Dispute Resolution System in Indonesian Courts: Pembaharuan Sistem Penyelesaian Perkara Hutang Piutang di Pengadilan Indonesia - Iyan Sentosa Zalukhu; Gunardi Lie (Academia Open, 2025)
General Background: The Indonesian civil justice system continues to face structural inefficiencies, including case backlogs, slow proceedings, and high litigation costs. Specific Background: These challenges are especially evident in resolving debt-related default disputes, where creditors—particularly concurrent creditors—often encounter uncertainty and weak enforcement. Knowledge Gap: Despite existing litigation and alternative dispute resolution (ADR) mechanisms, limited effectiveness, inconsistent legal certainty, and gaps in legal culture hinder optimal dispute settlement. Aims: This study analyzes the mechanisms for resolving debt-default disputes, the protection available for concurrent creditors, the application of legal certainty principles, and strategies to strengthen legal culture. Results: Findings show that dispute settlement operates through litigation and ADR; concurrent creditors receive preventive and repressive protections; legal certainty is grounded in Articles 1131–1132 of the Civil Code; and improving legal culture requires education, consistent enforcement, and institutional reform. Novelty: This research integrates doctrinal analysis with empirical judicial data to highlight systemic shortcomings in current debt-dispute resolution, particularly regarding creditor vulnerability and uneven implementation of reform policies. Implications: Strengthening legal frameworks, institutional capacity, and public legal awareness is essential to achieving a faster, simpler, and more affordable civil justice system in Indonesia. Highlights: Highlights the dual mechanisms of resolving debt-default disputes through litigation and ADR. Emphasizes the vulnerability of concurrent creditors and the need for stronger legal certainty. Underscores the importance of legal-culture development to support effective justice reform. Keywords: Debt Dispute Resolution, Legal Certainty, Concurrent Creditors, Civil Justice Reform, Legal Culture